SNOW TRANSPORT EQUIPMENT - TRACTOR-MOUNTED SNOWPLOW TESTS - Hansen,Robert W. (1964)
During the summer season of Deep Freeze 63, tests were made with a tractor-mounted snowplow to determine its suitability for clearing drift in a surface camp on snow and for transporting construction fill snow. The tests were made at the NCEL camp on the Ross Ice Shelf near McMurdo Station, Antarctica, in air temperatures ranging between 15 F and 30 F. Mechanical performance of the tractor-plow unit was satisfactory except for high mortality of the auger shear bolts. The 14 psi track bearing pressure necessitated a hard, firm working surface for the unit. This limited its use for clearing camp drift and hampered its efficiency for transporting fill snow. Even so, it was six times faster than the snow plane used in Deep Freeze 62. A special test where the plow was used to cast freshly windrowed snow from an exttemely hard surface showed that the plow's efficiency should be increased from 20 to 75% if it was properly supported. It was concluded that the investigation on the transport of construction fill snow with a snowplow should be continued using the ski-mounted, towed-type snowplow carrier concept developed during the Deep Freeze 63 tests. (Author)